Additional time in soccer - Siegle, M.; Prusharpner, R. (International Journal of Performance Analysis in Sport, 2013)
This study analysed additional time in soccer referees added on at the end of a match, during the 2012 European Championship. An observational system was used to analyse duration and number of occurrences of relevant game interruptions, indicated additional time and actual additional time. All 31 matches of the tournament were analysed, resulting in a total number of 196 relevant interruptions with a mean duration of 261.3 ± 86.5 s per match; average additional time per match was 218.1 ± 50.0 s. Maximum difference between relevant interruptions and additional time was 211 s. For 51% of all matches, additional time was too short. Results of ANOVA revealed that score has no significant influence on this phenomenon.